Occurrence of the genes encoding carbapenemases, ESBLs and class 1 integron‐integrase among fermenting and non‐fermenting bacteria from retail goat meat. (31st August 2020) - Singh, F.; Hirpurkar, S.D.; Rawat, N.; Shakya, S.; Kumar, R.; Rajput, P.K.; Kumar, S.
Abstract: The present study was planned to detect the genes encoding carbapenemases, ESBLs and class 1 integron‐integrase among bacteria obtained from retail goat meat. Fermenting and non‐fermenting bacterial isolates ( n = 57), recovered from 61 goat meat samples, were identified by 16S rRNA gene sequencing. Antimicrobial susceptibility of isolates was tested by the broth dilution method using ceftazidime, cefotaxime, meropenem and imipenem. Plasmids were isolated and tested for their physical characters. Plasmids were subjected to screening of carbapenemase, ESBL and intI1 gene. Conjugation assay was performed using bla NDM ‐positive isolates as the donor, and Escherichia coli HB101 as the recipient. Isolates showed the high rates of resistance to ceftazidime (77·2%), cefotaxime (70·2%), meropenem (22·8%) and imipenem (17·5%). They showed variability in number and size ( 1 to >20 kb) of plasmids. Among all, 1, 4, 13 and 31 isolates showed the bla KPC, bla NDM, bla SHV and bla TEM genes, respectively. The bla KPC‐2 gene was observed in one E. coli isolate. The bla NDM‐1 gene was detected in Stenotrophomonas maltophilia ( n = 2), Acinetobacter baumannii ( n = 1) and Ochrobactrum anthropi ( n = 1) isolates. These isolates co‐harboured the bla TEM and bla SHV genes. The intI1 gene was detected in 22 (38·6%) isolates, and 16 of these isolates showed the carbapenemase and/or ESBL genes. The conjugative movement of bla NDM gene could not be proved after three repetitive mating experiments. The presence of genes encoding carbapenemases and ESBLs in bacteria from goat meat poses public health risks. Abstract : Significance and impact of the study: The emergence of carbapenemases and extended‐spectrum β‐lactamases (ESBLs) in bacteria has now become a global problem leading to failure of advanced antimicrobial therapy. We report for the first time the bla NDM‐1 gene in non‐fermenting Gram‐negative bacterial isolates, and the bla KPC‐2 gene in an Escherichia coli isolate from goat meat in India. The presence of carbapenemase genes in bacteria from goat meat develops serious concerns about public health and food safety. Analysis of genetic determinants of β‐lactam resistance in bacteria would be helpful to formulate a suitable control strategy.